Validasi Metode Analisis Konsentrasi Larutan Kopi berdasarkan Spektroskopi Absorpsi Cahaya - Fajri, Nurullina; Prima, Eka Cahya; Riandi, Riandi; Sriyati, Siti (Universitas Nurul Huda, 2024)
This research aims to validate the method of analyzing the concentration of coffee solution by measuring light absorbance using simple spectrophotometry. Spectrophotometry is a technique that utilizes the interaction between visible light and electromagnetic waves on a substance. Measurement of the absorbency of the coffee was carried out by making five samples of coffee solution with different concentrations, namely 100 ppm, 160 ppm, 200 ppm, 350 ppm and 400 ppm. Absorbance measurements were carried out at visible light wavelengths (380 750 nm). The validation of the coffee has good linearity with a correlation coefficient of 0.9818; 0.9902 and 0.9788. The average precision value for the three treatments was 0.0056% with a Limit of Detection (LOD) and Limit of Quantitation (LOQ) of 115 ppm and 383.33 ppm for ( 405 nm 10); 44 ppm and 146.67 ppm for ( 532 nm 10); 70.2 ppm and 234 ppm for ( 650 nm 10). This indicates that the validation result of absorbance analytical method of the coffee, using simple spectrophotometry is not different from the standard measurement.